New biliary and pancreatic biodegradable stent placement: a single-center, prospective, pilot study (with video) - Anderloni, Andrea; Fugazza, Alessandro; Maroni, Luca; Ormando, Vittorio; Maselli, Roberta; Carrara, Silvia; Cappello, Annalisa; Mangiavillano, Benedetto; Omodei, Paolo; Preatoni, Paoletta; Galtieri, Piera Alessia; Pellegatta, Gaia; et al. (Gastrointestinal endoscopy, 2020)
In recent years, the feasibility and safety of endoscopic placement of different biodegradable biliary stents have been investigated. New, helicoidally shaped, biliary and pancreatic biodegradable stents have been developed for endoscopic use. Stents are provided in different sizes and with 3 expected speeds of degradation: slow (11 weeks), medium (20 days), and fast (12 days). The aim of this study was to evaluate degradation time, technical outcomes, and safety of these stents. This was a single-center, prospective, pilot study (August 2018 to January 2019) of consecutive patients with indication for biliary or pancreatic plastic stent positioning during ERCP. The primary outcome was the evaluation of degradation time of the stents, which was controlled by abdominal radiograph. Secondary outcomes were the evaluation of specific stent-related technical features (loadability, pushability, and fluoroscopic visibility) as compared with commonly used plastic stents and adverse events (AEs). Thirty-eight patients (11 women [28.9%]; median age, 68.05 ± 10.74 years) who received 53 biodegradable stents (34 [64.2%] biliary and 19 [35.8%] pancreatic stents) were enrolled in the study. Thirty-five (66%) slow-degrading stents, 6 (11.3%) medium-degrading stents, and 12 (22.6%) fast-degrading stents were used. At time 1, partial degradation of the stents was present in 48 cases (90.6%). Five stents (9.4%) prematurely migrated. At the subsequent time 2 evaluation, complete degradation occurred in 100% of cases. Stent loadability was defined as excellent in all cases. Pushability of the stent was scored as excellent in 48 cases (90.5%), good in 4 cases (7.5%), and fair in 1 case (1.9%). Fluoroscopic visualization was excellent in 11 cases (20.8%), good in 39 cases (73.6%), and fair in 3 (5.6%). Only 1 AE of mild post-ERCP pancreatitis occurred. The results of our study suggest that the biodegradation of the new biliary and pancreatic stents is reliable and in line with expected times and technically successful in a variety of indications. Further randomized multicenter studies are required to validate our preliminary findings. (Clinical trial registration number: NCT03767166.)